Kebijakan Formulasi Hukum Pidana terhadap Hak Anak Sebagai Pelaku Tindak Pidana dalam Undang-Undang Nomor 35 Tahun 2014 Tentang Perubahan Atas Undang-Undang Nomor 23 Tahun 2002 Tentang Perlindungan Anak - Nurhasan Nurhasan (Universitas Batanghari Jambi, 2019)
Today there are many perpetrators of crimes committed by minors. Such a thing has been proven because there has been a Juvenile Justice specifically dealing with child cases. In this case, the Judge in deciding a case carried out by minors rarely sees the rights of children as perpetrators of crimes, the Judge actually imposes criminal sanctions in accordance with the actions carried out by the child and often detained by law enforcement officers. This is the case, there is no listed children's rights as perpetrators of criminal acts in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection. Even though children are criminals, they should receive the same treatment as other children. The reason for the emergence of Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is to provide guarantees for the fulfillment of their rights without discrimination and violence, especially sexual violence. Then the implication if a regulation on the rights of children is held as a criminal offender in Law Number 35 of 2014 concerning Amendment to Law Number 23 of 2002 concerning Child Protection is to protect children in the face of the law from the arbitrariness of law enforcement officials and the child remains get a decent education so that they can change the character of him who was evil to be better than the previous one. then the policy on the formulation of future criminal law relating to children's rights as perpetrators of criminal acts in Law Number 35 of 2014 concerning Amendments to Law Number 23 of 2002 concerning Child Protection is a need to regulate the rights of children as perpetrators of crimes in order to realize children smart kids